2022
DOI: 10.3390/foods11182762
|View full text |Cite
|
Sign up to set email alerts
|

The Formation, Structural Characteristics, Absorption Pathways and Bioavailability of Calcium–Peptide Chelates

Abstract: Calcium is one of the most important mineral elements in the human body and is closely related to the maintenance of human health. To prevent calcium deficiency, various calcium supplements have been developed, but their application tends to be limited by low calcium content and highly irritating effects on the stomach, among other side effects. Recently, calcium–peptide chelates, which have excellent stability and are easily absorbed, have received attention as an alternative emerging calcium supplement. Calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 98 publications
(138 reference statements)
0
16
0
Order By: Relevance
“…Studies have shown that the chelating ability of peptides has a correlation with molecular weight, sequence and amino acid composition. 19 Thus, the sequence of DSPs was determined by Nano LC-MS/MS and the total ion flow chromatogram was obtained (Fig. 2).…”
Section: Peptide Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the chelating ability of peptides has a correlation with molecular weight, sequence and amino acid composition. 19 Thus, the sequence of DSPs was determined by Nano LC-MS/MS and the total ion flow chromatogram was obtained (Fig. 2).…”
Section: Peptide Sequence Analysismentioning
confidence: 99%
“…18 Therefore, peptide-calcium chelates can be used as a new type of nutritional supplement that can not only promote calcium absorption, but also provide functional active peptides to the consumer, playing a dual role. 19 The development of deer products as food and dietary supplements has gained attention over the past decade or so. Among these products, consumption of venison has increased due to its unique flavor, resulting in a large amount of by-products from slaughterhouses.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the amount of calcium that is absorbed by the human body can vary significantly. In recent years, researchers have been exploring ways to improve the absorption of calcium in the human body, and one of the most promising strategies to enhance calcium absorption is to use calcium-binding peptides derived from dietary proteins. …”
Section: Introductionmentioning
confidence: 99%
“…Peptides are absorbed by the PepT1 pathway, which is a proton-coupled transport system that moves peptides across the epithelial cells. 12,14 Calcium ions are absorbed by the TRPV6 pathway, which is a protein channel that facilitates calcium entry into the epithelial cells. 15,16 When calcium intake is normal or high, calcium can also be absorbed by the paracellular pathway, which involves either simple diffusion through the tight junctions or the formation of a calcium channel complex.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation